Pliocene sand injectites from a submarine lobe fringe during hydrocarbon migration and salt diapirism: a seismic example from the Lower Congo Basin. Issue 1 (17th October 2013) - Monnier, D.; Imbert, P.; Gay, A.; Mourgues, R.; Lopez, M.
Abstract Large‐scale conical and saucer‐shaped sand injectites have been identified in the Upper Miocene sediments of the Lower Congo Basin. These structures are evidenced on the 3D high‐resolution seismic data at about 600 ms TWT (two‐way traveltime) beneath the seabed. The conical and saucer‐shaped anomalies range from 20 to 80 m in height, 50 to 300 m in diameter, and 10 to 20 ms TWT in thickness. They are located within a sedimentary interval of about 100 m in thickness and are aligned over 20 km in dip direction (NE‐SW), above the NW margin of an underlying Upper Miocene submarine fan. We have interpreted the conical and saucer‐shaped anomalies as upward‐emplaced sand injectites sourced from the Upper Miocene fan because of their discordant character, the postsedimentary uplifting of the sediments overlying the cones and saucer‐shaped bodies, the alignment with the lateral fringe of the Upper Miocene submarine fan, and the geological context. Sand injection dates from the Miocene–Pliocene transition (approximately 5.3 Ma). The prerequisite overpressure to the sand injection process may be due to the buoyancy effect of hydrocarbons accumulated in the margins of the fan. Additionally, overpressure could have been enhanced by the lateral transfer of fluids operating in the inclined margins of the lobe. The short duration of sand injection and the presence of many sandstone intrusions suggested that the process of injection was triggered by an event, likely due to a nearby fault displacement related to diapiric movements. This is the first time that sand injectites of seismic scale have been described from the Lower Congo Basin. The localized nature of these injectites has led to a change in the migration path of fluids through the sedimentary cover. Consequently, the sand intrusions are both evidence and vectors of fluid migration within the basin fill.